Reports on COVID-19 Vaccines and Vaccination in Nigeria - Azike, Chidimma Anthonia; Konne Felix Eedee; Orudukobipi, Tamunonengiye-Ofori; Ben-Chioma, Adline Erinma; Nwibani, Albert Lesere (Archives of Current Research International, 2021)
A biological material intentionally prepared by scientists to provide active acquired immunity against a specific infectious disease is called a vaccine. It is engineered with either a portion of the pathogen that is harmless, or a whole pathogen but which has been killed or rendered harmless in the laboratory through radiation, chemical, or high temperature. The idea is to cause the body’s immune system to recognize the pathogen and to build immunity against it, should the body be exposed to it at any time. Categories of vaccines exists such as; prophylactics (which acts by preventing the effect of future infection by either natural or wild pathogen), and/or therapeutic (developed to fight a disease that has already occurred). This review is focused at understudying the various brands of vaccines approved by the World Health Organization (WHO) for covid, their mechanism of actions and the outcomes of these vaccines (benefits and adverse effects). The vaccines approved by WHO includes: the Oxford AstraZeneca, Pfizer BioNTech, Sputnik V, Sinopharm, Sinovac, Moderna and Convidecia each having its mode of action. Few mild adverse reactions have been noted so far from the administration of the vaccine and they include: pain at the site of injection, fever, dizziness, headache, and body aches which lasted from few hours of receiving the vaccines to about 24 hours. Some severe adverse reactions have also been observed. The benefits of taking the vaccine however far exceed these adverse effects. Finally, this study went further to examine the effectiveness of these vaccines against the Alpha, Gamma, Beta, and Delta variants of COVID-19 and was found to be able to offer immunity against them.